Climate Change and Gender-responsive Policies: A Case Study in Semarang, Central Java, Indonesia - Rusmadi, Rusmadi; Hadi, Sudharto P.; Purnaweni, Hartuti (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2025)
Semarang City is a coastal city facing serious problems related to climate change impacts, both in its physical environment and social vulnerability. Climate change does not occur in a vacuum, but manifests within a complex of social spaces, including gender relations. Referring to such a socio-ecological perspective, this study attempts to analyze the operational mechanism of climate change by reviewing gender relations as their spatial-social dimension. Simultaneously, this study examines the extent to which climate resilience policies in Semarang City have integrated considerations of the social space. Data collection was conducted through observation, interviews, FGD, and review of Semarang City's climate resilience policy documents. Descriptive analysis was used to describe how exposure to climate change impacts men and women, while content analysis was used to examine Semarang City's climate resilience policies. The findings indicate that socio-ecological vulnerability is more prevalent among women's groups than men's. It is evident that as women experience more exposure to climate change impacts, and at the same time, the issues of women's vulnerability are not prioritized in climate resilience policies. This research recommends more just, socio-ecological governance in building climate resilience.